Perempuan Minang Pada Novel Segala Yang Diisap Langit Karya Pinto AnugrahKajian Strukturalisme Genetik Goldmann - Kamila Nur Azizah; Syamsul Sodiq (CV. SINAR HOWUHOWU, 2026)
This study aims to reveal the worldview of Minang noblewomen, the socio-historical context, and the homological relationship between the conflict in Pinto Anugrah’s novel Segala yang Diisap Langit and the historical reality of the Padri War. Employing a qualitative approach and Lucien Goldmann’s genetic structuralism theory, data comprising narrative excerpts, dialogue, and events from the novel were collected through reading-and-noting techniques and literature review. The analysis proceeded in three stages: understanding the text’s structure, explaining the socio-historical context, and analyzing the homological relationship. The study yielded three main findings. First, the worldview of Minang noblewomen is represented through the characters Rabiah and Jintan Itam as guardians of the lineage, women who boldly make decisions, and women living amidst beliefs in myths and curses. Second, the novel’s socio-historical context depicts the decadence of the nobility, the emergence of the Padri movement, and the ideological conflict between matrilineal custom and the patriarchal value system. Third, a homological relationship was identified between the conflict in the novel and the history of the Padri War, particularly regarding characters, value systems, symbols of violence, and conflict resolution. Through this relationship, the author conveys a critique of violence while honoring the resilience of Minang women in preserving their cultural identity.